Research trends on occupational stress of female employees: a bibliometric analysis - Sultana, Nafia; Subramaniam, Anusuiya; Wong, Foong Yee (UiTM Press, 2023)
The study aims to examine the research trends on occupational stress of female employees between the period of 1973 to 2022 using bibliometric analysis. A total of 508 research documents have been analysed in the study. A systematic process flow has been followed to extract the research documents from the Scopus database. The findings from the analysis showed that the research trends on occupational stress of female employees have ups and downs since the beginning. Based on the highest publications to the related research on occupational stress of women, Finland has been placed as the most productive country, followed by the United States, Sweden and United Kingdom. The most active authors are Kivimäki, Vahtera J and Virtanen in terms of number of publications and number of total citations. Several future research areas have been identified from the results of the VOSviewer networking map. It is found from the growing number of author keywords in the literature are stress, gender, mental health, occupational health and working conditions which have potential literature gaps to work on in future. The results of the study have also opened a new avenue for the future researchers and industry practitioners to work on occupational stress related issues to understand the cause and consequences of it.